Pengaruh Profitabilitas dan Leverage terhadap Harga Saham Perusahaan Manufaktur di Bursa Efek Indonesia - Saprudin Saprudin; Tufrida Murniati Hasyim (Lembaga Penelitian Universitas YARSI, 2020)
This study aimed to determine the relationship between managerial ownership, leverage, and profitability to the stock prices of manufacturing companies listed on the Stock Exchange for the period 2015 to 2017. Profitability is proxied by Return on Equity (ROE), while leverage is proxied by Debt to Equity Ratio (DER). The stock price applied was the closing rate of the year-end stock. Sampling was done by using purposive sampling method. The subject of the study was 30 manufacturing companies with a total of 90 observations. The data analysis utilised multiple regression analysis with the help of the SPSS program. Based on the results of the study, it was found that the profitability had a significant effect on stock prices, and leverage did not affect stock prices. Together, profitability and leverage did not have a significant effect on stock prices. Thus, the company must pay more attention to the profitability of the business in order to maintain a good price of the stock and to attract investors.